Lightness dependence of achromatic loci in color-appearance coordinates - Kuriki, Ichiro (Frontiers in Psychology, 2015)
Shifts in the appearance of color under different illuminant chromaticity are known to be incomplete, and fit nicely with a simple linear transformation of cone responses that aligns the achromatic points under two illuminants. Most chromaticity-transfer functions with von-Kries-like transformations use only one set of values to fit the color shifts from one illuminant to another. However, an achromatic point shifts its chromaticity depending on the lightness of the test stimulus. This lightness dependence of the achromatic-point locus is qualitatively similar to a phenomenon known as the Helson-Judd effect. The present study suggests that the lightness dependency of achromatic points appears to be a general trend, which is supported by the results from deriving the optimal von-Kries coefficients for different lightness levels that best fit the color shifts under different illuminant chromaticities. Further, we report that such a lightness dependence of the achromatic-point loci can be represented simply as a straight line in coordinates defined using color-appearance models such as CIECAM when normalized for daylight.